PUPUK PHOSPHO-KOMPOS ORGANIK YANG DIPERKAYA DENGAN MIKROORGANISME PELARUT P DAN PENGARUHNYA TERHADAP PERTUMBUHAN RUMPUT Setaria splendida - Dianita, Rahmi; Rahman, A.; Ubaidillah, Sy. (Pastura, 2014)
The aimed of this experiment was to investigate the effect phosphorus-enriched compost fertilizer with P solubilizing microorganisms on the growth of Setaria splendida. The experiment was designed in completely randomized designed with 4 treatments, consisted of R0 = Rock phosphate, R1 = Rock phosphate + rice straw + chicken manure, R2 = Rock phosphate +  rice straw + chicken manure + Trichoderma harzianum. R3 = Rock phosphate + rice straw+ chicken manure + Aspergillus niger. Preparation of phosphorus-enriched compost was modified from Bangar et al. (1989); Biswas (2008) with the dosage of aplication based on Apniyarni, (2003) and Dewi (2002). Physical and chemical characteristics of phosphorus-enriched compost fertilizer and the growth of S. splendida were observed in this experiments. The results showed that phosphorus- enriched compost fertilizer with and without P solubilizing microorganisms resulted good physical and chemical characteristics. The growth of S. splendida did not significantly different for phosphorus-enriched compost with and without P solubilizing microorganism treatments. Application of enriched phospho-compost fertilizer with and without P solubilizing microorganisms significantly increased the growth of S. splendida compared to control (rock phosphate).
Keywords: Aspergillus niger, enriched phospho-compost organic, S. splendida, Trichoderma harzianum